Evaluation of the Effectiveness of Government Policy on MSMEs Through Empirical Data Analysis in Lampung - Warsiyah; Saputeri, Noorikha Pandayahesti; Nurulia, Eki Tiyas; Fakhrurozi, Moh (2024)
Micro, Small, and Medium Enterprises (MSMEs) play an important role in the Indonesian economy, including in Lampung Province. Although the government has issued various policies to support the development of MSMEs, the effectiveness of these policies still needs to be evaluated in depth. This research aims to evaluate the effectiveness of government policies in supporting MSMEs in Lampung through empirical data analysis. The research uses an empirical data analysis approach to evaluate the effectiveness of MSME support policies in Lampung. The analytical method in this research uses literature study through collecting and analyzing secondary data in the form of journal articles, government documents, and other scientific articles about entrepreneurship and MSMEs sourced from libraries. It is hoped that the results of this research will provide a comprehensive evaluation of the effectiveness of government policies in supporting MSMEs in Lampung, as well as identifying supporting and inhibiting factors for policy success. This research found that government policy in supporting MSMEs in Lampung had a positive impact in encouraging the growth of the MSME sector in Lampung. However, there are still challenges that still need improvement, namely lack of socialization, and limited access for MSMEs in remote areas.